BETWEEN THE BOOK AND GOOGLE CLASSROOM: ISLAMIC JURISPRUDENCE EDUCATION IN THE DIGITAL ERA - Iqbal Ramadhan Irsyad Yudiono; Pratiwi Rahmah Hakim; Abdurrahman Hadi; Fadhel Ikhlasul Amal Makalitutu; Milevtra Myoriuke; Ayman Hammam Abdurrohman (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
ABSTRACT The rapid advancement of digital technology has brought fundamental changes to educational practices, including fiqh learning, which has traditionally been dominated by classical text-based approaches. This transformation calls for the development of a learning model capable of bridging the depth of Islamic scholarly traditions with the flexibility of digital environments. This study aims to analyze how the integration of classical fiqh texts and digital platforms can maintain epistemological depth while enhancing learning relevance. The research employs a qualitative approach using a library research design, analyzing 26 academic sources published within the last ten years. Data were examined through stages of selection, thematic categorization, and interpretation to identify patterns of integration, advantages, and emerging challenges. The findings indicate that the use of digital platforms expands access to learning materials, promotes independent learning, and enhances interaction through multimodal media and online discussion spaces. However, several challenges remain, including limited digital competence among educators, suboptimal instructional design, and reduced intensity of pedagogical interaction, which may affect the transmission of adab and spiritual values. This study concludes that a value-based integration model is needed, positioning digital technology as a supporting medium rather than a replacement for traditional scholarship. The implementation of this model requires strengthening teacher capacity, institutional support, and pedagogical alignment to ensure that innovation remains grounded in the ethical and intellectual values of Islamic education. ABSTRAK Perkembangan pesat teknologi digital telah membawa perubahan mendasar dalam praktik pendidikan, termasuk dalam pembelajaran fiqh yang selama ini didominasi oleh pendekatan berbasis kitab klasik. Perubahan ini menuntut adanya formulasi model pembelajaran yang mampu menghubungkan kedalaman tradisi keilmuan Islam dengan fleksibilitas lingkungan digital. Penelitian ini bertujuan untuk menganalisis bagaimana integrasi antara teks klasik fiqh dan platform digital dapat mempertahankan kedalaman epistemologis sekaligus meningkatkan relevansi pembelajaran. Penelitian menggunakan pendekatan kualitatif dengan desain library research, dengan menganalisis 26 sumber akademik yang terbit dalam sepuluh tahun terakhir. Data dianalisis melalui tahapan seleksi, kategorisasi tematik, dan interpretasi untuk mengidentifikasi pola integrasi, kelebihan, serta tantangan yang muncul. Hasil penelitian menunjukkan bahwa pemanfaatan platform digital mampu memperluas akses terhadap materi, mendorong kemandirian belajar, serta meningkatkan interaksi melalui penggunaan media multimodal dan ruang diskusi daring. Namun demikian, terdapat sejumlah kendala, seperti keterbatasan kompetensi digital pendidik, kualitas desain pembelajaran yang belum optimal, serta berkurangnya intensitas interaksi pedagogis yang berpengaruh pada penanaman nilai adab dan spiritualitas. Penelitian ini menyimpulkan bahwa diperlukan model integrasi berbasis nilai yang menempatkan teknologi digital sebagai media pendukung, bukan pengganti tradisi keilmuan. Implementasi model ini memerlukan penguatan kapasitas pendidik, dukungan institusi, serta keselarasan pedagogis agar inovasi tetap berakar pada nilai etika dan intelektual pendidikan Islam.